Letter-Sound Knowledge: Exploring Gender Differences in Children When They Start School Regarding Knowledge of Large Letters, Small Letters, Sound Large Letters, and Sound Small Letters - Sigmundsson, Hermundur; Eriksen, Adrian D.; Ofteland, Greta Storm; Haga, Monika (Frontiers in Psychology, 2017)
This study explored whether there is a gender difference in letter-sound knowledge when children start at school. 485 children aged 5-6 years completed assessment of letter-sound knowledge i.e. large letters; sound of the large letter; small letters; sound of the small letters. The findings indicate a significant difference between girls and boys in all four factors tested in this study in favour of the girls. There are still no clear explanations to the basis of a presumed gender difference in letter-sound knowledge. That the findings have origin in neuro-biological factors cannot be excluded, however, the fact that girls probably have been exposed to more language experience/stimulation compared to boys, lends support to explanations derived from environmental aspects.